USE OF BIOMONITOR EUROPEAN ASH (FRAXINUS EXCELSIOR L.) TREE FOR MONITORING TRAFFIC RELATED HEAVY METAL POLLUTION IN BISHKEK/KYRGYZSTAN: IMPACTS ON PLANT NUTRITION - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
Biomonitor organisms can be used to determine pollution levels and their regional distributions. In this sense, this study investigated traffic-related heavy metals pollution and its impact on plant nutrition by using biomonitor plant European ash (Fraxinus excelsior L.) tree. For this aim, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Pb and Zn levels were analyzed by using ICP-OES in plant and soil samples taken from eight different locations in Bishkek/Kyrgyzstan. Ca and Mg levels were highest at Shabdan Baatry Street (St2) while other remaining elements were highest at Chuy Street (St4). Chuy Street has been an international transit road with heavy traffic, thus increased levels of most elements were reasonable. Heavy metals Cd and Pb in soil, and Cd, Cr and Pb in plants were above the acceptable ranges but not toxic levels in plant samples. Removal rates of Cd, Cu, Mn and Pb between washed and unwashed leaves were higher than other elements at all stations. Except Ca and Na, all test metals demonstrated strong positive correlations. In light of these findings, the biomonitor plant F. excelsior could effectively reflect the pollution levels in Bishkek/Kyrgyzstan.
Keywords: Heavy metal; mineral nutrition; pollution; anthropogenic activity; toxicity; ACCUMULATION; TOXICITY; NUTRIENT; CALCIUM; SOILS; DETOXIFICATION; ISTANBUL; DAMAGE; GENES; SITES